2018
DOI: 10.1186/s13104-018-3440-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of back disorder among Almeda textile factory workers, North Ethiopia

Abstract: ObjectivesTo guide the development of targeted interventions for the prevention of work-related back pain, this manuscript estimates the prevalence of back pain and its association with a variety of risk factors among Almeda textile factory production works from March to April 2015. An institutional—based cross-sectional study was carried out in Almeda textile factory, North Ethiopia. Randomly selected workers were administered a structured questionnaire about their socio-economic status, lifestyle, working co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 8 publications
0
34
0
1
Order By: Relevance
“…Both textile and garment department workers have higher odds of MSDs compared to the support department workers. Other studies have showed the presence of ergonomic hazards both in the textile and garment department that could increase the risk of MSDs (27)(28)(29). Also, ergonomic hazard exposure assessment studies in Bangladesh and Cambodia found that the tasks in garment production gave high risk of MSDs (10,12).…”
Section: Work-related Factorsmentioning
confidence: 99%
“…Both textile and garment department workers have higher odds of MSDs compared to the support department workers. Other studies have showed the presence of ergonomic hazards both in the textile and garment department that could increase the risk of MSDs (27)(28)(29). Also, ergonomic hazard exposure assessment studies in Bangladesh and Cambodia found that the tasks in garment production gave high risk of MSDs (10,12).…”
Section: Work-related Factorsmentioning
confidence: 99%
“…Hal tersebut sejalan dengan penelitian lainnya yang menunjukkan pekerja yang tidak terbiasa melakukan aktivitas fisik lebih berisiko mengalami keluhan musculoskeletal disorder. (9) Masa kerja responden penelitian sebagian besar <5 tahun (66%). Masa kerja tersebut telah mampu memberikan kontribusi terhadap munculnya keluhan musculoskeletal disorder.…”
Section: Tabel 1 Karakteristik Responden Penelitianunclassified
“…However, musculoskeletal disorders remain a major global health concern and an immense burden for LMICs like Ethiopia where health budgets are already constrained and channeled life-threatening conditions. Studies have shown that musculoskeletal pain prevalence among the working population in Ethiopia varies from 35% to 74.5% [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%